2008
DOI: 10.1037/1942-9681.s.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of posttraumatic stress disorder and symptoms in adults: A meta-analysis.

Abstract: A review of 2,647 studies of posttraumatic stress disorder (PTSD) yielded 476 potential candidates for a meta-analysis of predictors of PTSD or of its symptoms. From these, 68 studies met criteria for inclusion in a meta-analysis of 7 predictors: (a) prior trauma, (b) prior psychological adjustment, (c) family history of psychopathology, (d) perceived life threat during the trauma, (e) posttrauma social support, (f) peritraumatic emotional responses, and (g) peritraumatic dissociation. All yielded significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

67
909
14
41

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(1,031 citation statements)
references
References 138 publications
67
909
14
41
Order By: Relevance
“…Estimated clinical caseness for post-traumatic stress symptoms was high for both groups compared to estimates of lifetime PTSD prevalence of 5–10% in the general population (Ozer, Best, Lipsey, & Weiss, 2008). Although many patients in both groups scored above the cut-off for clinical post-traumatic stress symptoms, the reported symptoms only correlated with the sum of CMT for the SUD group, suggesting a stronger and possibly more direct association between CMT and post-traumatic stress symptoms for these patients.…”
Section: Discussionmentioning
confidence: 73%
“…Estimated clinical caseness for post-traumatic stress symptoms was high for both groups compared to estimates of lifetime PTSD prevalence of 5–10% in the general population (Ozer, Best, Lipsey, & Weiss, 2008). Although many patients in both groups scored above the cut-off for clinical post-traumatic stress symptoms, the reported symptoms only correlated with the sum of CMT for the SUD group, suggesting a stronger and possibly more direct association between CMT and post-traumatic stress symptoms for these patients.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to gender and age, prior exposure to traumatic events is also a pre-trauma characteristic that can contribute to earthquake survivors' vulnerability. Previous studies suggested that exposure to a traumatic event may make individuals vulnerable to the negative effects of subsequent traumas, creating more intense posttraumatic stress [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Inferring PTSD prevalence after a traumatic event in hospital settings simply from a certain cohort study is noticeably inaccurate. Initial symptom severity and prior mental illness can be strong risk factors for later PTSD (Brewin et al, 2000; Ozer et al, 2003). Furthermore, epidemiological studies also reported higher prevalence of PTSD in women, in people living in areas with high community violence, and in victims of interpersonal trauma (Breslau, Chilcoat, Kessler, & Davis, 1999; Breslau et al, 1998; Goldmann et al, 2011; McLean, Asnaani, Litz, & Hofmann, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies (reviewed below) have typically annotated the type of traumatic event, participants’ symptoms, and information about known PTSD predictors, such as gender, lifetime trauma exposure, prior mental illness, education, and recovery environment (Brewin, Andrews, & Valentine, 2000; Bryant et al, 2012; Freedman et al, 2002; Gabert-Quillen et al, 2012; Koren, Arnon, & Klein, 1999; Macklin et al, 1998; Ozer, Best, Lipsey, & Weiss, 2003), to evaluate prediction of non-remitting PTSD. These data constitute a viable source for inferring risk estimates across different studies, while reflecting the specific culture and context in which each study was conducted.…”
Section: Introductionmentioning
confidence: 99%